Bioequivalence of Acenocoumarol in Chilean Volunteers: an Open, Randomized, Double-Blind, Single-Dose, 2-Period, and 2-Sequence Crossover Study for 2 Oral Formulations - Sasso, J.; Carmona, P.; Quiñones, L.; Ortiz, M.; Tamayo, E.; Varela, N.; Cáceres, D.; Saavedra, I. (Arzneimittelforschung, 2012)
The aim of this study was to compare the bioavailability of an oral formulation of the coumarin derivative-vitamine K antagonist acenocoumarol (AcebronTM 4 mg, Test) with the reference formulation (Neo-SintromTM 4 mg). We performed a single-dose, double-blind, fasting, 2-period, 2-sequence, crossover study design. Plasma concentrations of acenocoumarol were determined using a validated UPLC-MS/MS method. 24 healthy Chilean volunteers (11 male, 13 female) were enrolled and all of them completed the study. Adverse events were monitored throughout the study. The values of the pharmacokinetic parameters were (mean ± SD): AUC0-24  =1 364.38±499.26 ngxh/mL for the test and 1 328.39±429.20 ngxh/mL for the reference; AUC0-∞  =1 786.00±732.85 ngxh/mL for the test and 1 706.71±599.66 ngxh/mL for the reference; Cmax  =180.69±35.11 ng/mL with a Tmax of 1.83±0.95 h for the test and 186.97±38.21 ng/mL with a Tmax of 2.19±0.83 h for the reference. Regarding half life measurements, the mean ± SD of t1/2 were 11.84±4.54 h for the test and 11.08±3.28 h for the reference. The 90% confidence intervals for the test/reference ratio using logarithmic transformed data were 97.89–100.87%, 98.62–101.99% and 98.64–102.38% for Cmax, AUC0-t(24) and AUC0–∞. There were no significant differences in pharmacokinetic parameters between groups.The results obtained in this study lead us to conclude, based on FDA criteria, that the test acenocoumarol formulation (AcebronTM, 4 mg tablets) is bioequivalent to the reference product (Neo-SintromTM, 4 mg tablets).
Keywords: therapeutic equivalence; pharmacokinetics; pharmaceutics anticoagulant; drug regulation